1986
DOI: 10.1111/j.1365-2133.1986.tb05740.x
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind controlled cross-over trial of cyproterone acetate in females with hidradenitis suppurativa

Abstract: In order to examine whether anti-androgen therapy was effective in hidradenitis suppurativa (HS), ethinyloestradiol 50 micrograms/cyproterone acetate 50 mg in a reverse sequential regimen was compared with ethinyloestradiol 50 micrograms/norgestrel 500 micrograms (Eugynon 50) in 24 female patients. Both treatments produced substantial improvement in disease activity. Seven patients cleared and have remained free of disease for 18 months, five patients improved, four remained unchanged, while two deteriorated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0
7

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(103 citation statements)
references
References 5 publications
2
94
0
7
Order By: Relevance
“…Recurrent disease-Disease recurred locally at 21 sites in 19 patients, developing from three to 72 months (median 24 months) after operation in 15 patients after inguinoperineal surgery, in three after axillary excision, and in three after mammary excisions, giving recurrence rates of 37%, 3%, and 50%, respectively. There was no local recurrence after operation for perianal disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recurrent disease-Disease recurred locally at 21 sites in 19 patients, developing from three to 72 months (median 24 months) after operation in 15 patients after inguinoperineal surgery, in three after axillary excision, and in three after mammary excisions, giving recurrence rates of 37%, 3%, and 50%, respectively. There was no local recurrence after operation for perianal disease.…”
Section: Resultsmentioning
confidence: 99%
“…Anatomy and subversion: 150th anniversary of Georg Buchner's death J L CRIGHTON Karl Georg Buchner died of typhus in Zurich on 19 February 1837 in his 24th year. Like the friends in whose home he had been cared for, and like Schonlein, one of the physicians who attended him, he was a refugee from the political oppression prevailing in the German states ofthe post-Metternich era.…”
Section: Medical Historymentioning
confidence: 99%
“…However, a doubleblind controlled trial comparing ethinyloestradiol 50 lg/cyproterone 50 mg with ethinyloestradiol 50 lg/ norgestrel 500 lg showed no difference between the two groups. However, of the 18 patients from both groups that completed the trial, 12 showed a good response, suggesting that both hormonal therapies can be effective in HS [131]. However, larger, well powered studies on the use of hormonal therapy in HS are lacking.…”
Section: Cyproterone Acetatementioning
confidence: 99%
“…Chronic lesions, on the other hand, can be treated in a number of ways, including antibiotics 3,4,17,18 , hormones 19 and biologics 20,21 . However, non-surgical approaches provide only temporary improvement and relief.…”
Section: Discussionmentioning
confidence: 99%